Qualitative decision making in adaptive presentation of structured information. - Brafman, Ronen I. (ACM transactions on information systems.)
We present a new approach for adaptive presentation of structured information, based on preference-based constrained optimization techniques rooted in qualitative decision-theory. In this approach, document presentation is viewed as a configuration problem whose goal is to determine the optimal presentation of a document, while taking into account the preferences of the content provider, viewer interaction with the browser, and, possibly, some layout constraints. The preferences of the content provider are represented by a CP-net, a graphical, qualitative preference model developed in Boutilier et al. [1999]. The layout constraints are represented as geometric constraints, integrated within the optimization process. We discuss the theoretical basis of our approach, as well as implemented prototype systems for Web pages and for general media-rich document presentation.